Acute hearing loss in febrile patients: a predictor of scrub typhus - Premaratna, R.; Chandrasena, T.G.A.N.; Dassanayake, A.S.; Loftis, A.; Dasch, G.A.; de Silva, H.J. (Sri Lanka Medical Association, 2005)
INTRODUCTION: Rickettsial infections are re-emerging in Sri Lanka. Complications such as pneumonitis, myocarditis and encephalitis can occur late in the disease, and result in a high mortality. Early diagnosis reduces morbidity and mortality, but as laboratory facilities for definitive diagnosis are lacking, early diagnosis depends on clinical suspicion. Acute hearing loss which occurs in about 30% of patients has been recognised as a predictor of scrub typhus. METHODS: Six patients admitted to hospital with high fever and hearing impairment were further investigated. RESULTS: All were females with a mean age of 65 years (SD 2). The mean duration of fever at presentation was 12 days (SD 1), Hearing impairment was observe<Hn all (deaf 4, tinnitus 2). In all 6 patients, rising litres of both IgM and IgG antibodies against scrub typhus were observed between acute and convalescent serum samples confirming the diagnosis of scrub typhus. The presence of deafness prompted the clinical diagnosis and institution of specific treatment. All 6 patients had pneumonitis. two patients had severe illness with myocarditis and encephalitis in addition to deafness and pneumonitis; one of them who presented late died despite appropriate treatment. The others improved rapidly with medication. CONCLUSIONS: The detection of acute hearing loss in these febrile patients facilitated the diagnosis of scrub typhus and lead to early institution of appropriate treatment.
Poster Presentation Abstract (PP8), 118th Annual Scientific Sessions, Sri Lanka Medical Association, 2005 Colombo, Sri Lanka
Keywords: Acute hearing loss